ANALISA PERBANDINGAN DATA PASANG SURUT DENGAN METODE KOEFISIEN KORELASI DAN RMSE ANTARA DATA IOC SEALEVELMONITORING DAN DATA PROGRAM NAOTID - Chaidir, Chaidir; Tuharea, Natasha Dewanti (Riset Sains dan Teknologi Kelautan, 2022)
Indonesia is a maritime country because it has a very wide geographical condition of the ocean with more than 17,000 islands. Ocean tides are the result of gravitational attraction and centrifugal effects, namely the push towards the outside of the center of rotation. There are two ways to determine the value of tides, the first is to measure directly in the field using a tide gauge or using a numerical modeling program. Therefore, this study intends to compare field data using the ioc-sealevelmonitoring website with tide prediction data using the Naotide program where the data collection point is at the tide station in Cilacap Regency, West Java, Indonesia. This research will produce tidal constituent data from the data and will calculate the RMSE (Root Mead Square Error) value and the correlation coefficient. Mead Square Error) and correlation coefficient of the data. The results show that the two variables can be said to be suitable as evidenced by the RMSE value which is close to 0 (zero) and the correlation coefficient which is in the range of 0.90 - 1.00 which means the correlation value is very high and reliable.